A study on launch vehicle on board acoustic data compression. (15th December 2020) - Coelho da Silva Stanisce Corrêa, Guilherme; Pirk, Rogério; da Silva Pinho, Marcelo
Abstract: The field of data compression has been evolved over the last decades. In this way, several techniques to reduce the amount of acquired data from the sensor required to be transmitted have been developed. Those techniques are usually classified by lossless or lossy, where, for the lossless techniques, all acquired data is recovered, while the lossy techniques introduce errors to these data. Each of these techniques presents advantages and drawbacks, being the analyst responsible for choosing the appropriate technique for a specific application. This work presents a comparison study using Vorbis lossy audio format with a low pass filter and a custom psychoacoustic masking curve to reduce the error in compressing a vibro-acoustic signal from a launch vehicle.